Lawyering from the inside out : learning professional development through mindfulness and emotional intelligence - Martin, Nathalie, 1961-; Alt, Joshua; Kerew, Kendall; Laws, Jennifer L.; Miller, Pamela Zen (Cambridge : Cambridge University Press, 2018)
Law is a varied, powerful, and highly rewarding profession. Studies show, however, that lawyers have higher rates of alcoholism, divorce, and even suicide than the general population. Stress creates these poor outcomes, including the stress of dealing with other people's problems all day, the stress of spending excessive amounts of time at work, and the stress of being disconnected to what is most meaningful in life. Through mindfulness and emotional intelligence training, lawyers can improve focus, get more work done in less time, improve their interpersonal skills, and seek and find work that will make their lives more meaningful. This book is designed to help law students and lawyers of all experience levels find a sustainable and meaningful life in the field of law. This book includes journaling and other interactive exercises that can help lawyers find peace, focus, meaning, and happiness over a lifetime of practicing law.
Machine generated contents note: Introduction; Part I. Nurturing Your Best Self: 1. Gaining self-awareness; 2. Introduction to mindfulness; 3. Managing energy, time, and physical space for happy and healthy efficiency; 4. The lawyer in society: popular culture images of lawyers and your self image; 5. Lawyer skill sets: what we have, what we need; 6. Building your professional identity; 7. Lawyer resilience; 8. Mindfulness theory and practice; Part II. You and Others Around You: 9. Emotional intelligence basics: theory and practice; 10. Advanced emotional intelligence; 11. Emotional intelligence on the page: the writer's life; 12. Giving and receiving feedback; 13. Empathy; 14. Cross-cultural lawyering; 15. Making mindful, client-centered decisions; Part III. You and Society: Finding Greater Purpose: 16. Purpose, creativity, happiness, and the practice of law; 17. Responsibility to society, professional identity, and access to justice; 18. Gratitude.
Title from publisher's bibliographic system (viewed on 29 May 2018).
Keywords: Practice of law -- Psychological aspects -- United States; Mindfulness (Psychology); Emotional intelligence